PENGARUH PIJAT WOLLWICH TERHADAP RERATA PRODUKSI ASI PADA IBU POSTPARTUM DI PMB LUSI KABUPATEN BANDUNG PADA TAHUN 2021 - Lusi Trianawati (Sekolah Tinggi Ilmu Kesehatan Rajawali, 2021)
Abstract Background: Many things can cause failure in the breastfeeding process, it can be from mother factors, baby factors or other problems. One of the main causes of this failure from maternal factors is anxiety, lack of confidence and mother's fear of lack of milk production. Therefore, it is necessary to make efforts to overcome these problems, one of which is the Wollwich massage method. The Wollwich massage method is a pleasant form of touch therapy, gently stimulating the nipples to cause oxytocin secretion. Objective: This study aims to determine how much influence Wollwich massage has on breast milk production in 6-hour postpartum mothers at PMB Lusi, Bandung Regency in 2021. Methods: This research is an experimental study that uses a quasi-experimental study with a nonequivalent control group design. The sample in this study were all 6-hour postpartum mothers who gave birth normally at PMB Lusi, the period April-June 2021 as many as 30 people. Where the total sample is divided into 2 groups, namely the intervention group / given treatment and control group / not given treatment. Data analysis using Wilcoxon test and Mann Whitney test. Results: The average milk production after giving Woolwich massage in the intervention group was 0.68 cc, the average milk production after giving breast massage in the control group was 0.29 cc and there were differences in the average milk production between postpartum mothers in the intervention group and the control group with p- value 0.002 < (0.05). Conclusion: There is an effect of Wollwich massage based on the average milk production produced in 6 hours postpartum mothers between the intervention group and the control group at PMB Lusi, Bandung Regency.